Cambridge Key English Test 2 - Cambridge University Press (Fahasa, 2011)
Authentic examination papers from cambridge esol;Official preparation material for cambridge english: Key, also known as Key english Tests (Ket); Cambridge KET 2 contains four complete papers for the Cambridge Key English Test from University of Cambridge ESOL Examinations. These past examination papers provide the most authentic exam preparation available. They allow candidates to familiarise themselves with the content and format of the examination and to practise useful examination techniques. These papers follow the March 2004 revised exam specifications